Clinical Case Reports: Current Challenges in Clinical Practice - Ribeiro Junior, Howard Lopes (Brazilian Journal of Case Reports, 2023)
Clinical Case Reports: Current Challenges in Clinical Practice is a comprehensive collection of 66 clinical case reports originally published in the Brazilian Journal of Case Reports during the biennium 2021–2022. This volume encompasses a wide range of multidisciplinary cases across the healthcare spectrum, from physiotherapy to diverse medical specialties. Each report provides unique insights into diagnostic and therapeutic challenges, highlighting innovative approaches and remarkable patient outcomes. By integrating clinical practice with scientific reflection, the book emphasizes the importance of case reports as powerful tools for advancing medical knowledge, guiding clinical decision-making, and inspiring continuous learning. Through the dedication of healthcare professionals, authors, and the editorial team, this compilation stands as both a testament to clinical excellence and a valuable reference for practitioners navigating the complexities of modern healthcare. ISBN: 978-65-981870-0-2 (PDF)